2015
DOI: 10.5851/kosfa.2015.35.5.622
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Replacing Sucrose with Various Sugar Alcohols on Quality Properties of Semi-dried Jerky

Abstract: The objective of this study was to investigate the effects of replacing sucrose with sugar alcohols (sorbitol, glycerol and xylitol) on the quality properties of semi-dried jerky. Total 7 treatments of jerkies were prepared as follows: control with sucrose, and treatments with 2.5 and 5.0% of sucrose replaced by each sugar alcohol, respectively. Drying yield, pH, water activity, moisture content, shear force, myofibrillar fragmentation index (MFI), 2-thiobarbituric acid reactive substance (TBARS) value, sugar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 24 publications
0
17
0
2
Order By: Relevance
“…Furthermore, the cookies formulated with the three sugar alcohols showed lower AV and PV than the sucrose control. This might be explained by the fact that the sugar alcohols could react with free radicals to form complexes that have a metal ion chelation ability to inhibit oxidation (Jang et al., 2015). The research of Wada, Kuragano, Fuse, and Takai (1978) found that maltitol was superior to sucrose in preventing lipid rancidity.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the cookies formulated with the three sugar alcohols showed lower AV and PV than the sucrose control. This might be explained by the fact that the sugar alcohols could react with free radicals to form complexes that have a metal ion chelation ability to inhibit oxidation (Jang et al., 2015). The research of Wada, Kuragano, Fuse, and Takai (1978) found that maltitol was superior to sucrose in preventing lipid rancidity.…”
Section: Resultsmentioning
confidence: 99%
“…Commercially this intermediate moisture foodstuff is often preserved using a hurdle concept involving interventions such as reducing aw through the addition of preservatives such as organic acids, spices and nitrate/nitrite salts. The development of whole-muscle and/or restructured jerky from a range of meats by employing various curing ingredients, curing methods and drying conditions have been widely reported (Choi et al, 2008;Jang et al, 2015;Kucerova et al, 2015). With growing consumer demand for high quality foods with good flavour, texture, nutrition and safety profiles, various strategies are being investigated and applied to jerky production.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the decrease in water activity with the addition of water to the sausage resulted from the increase in thermal conductivity, which accelerates the decrease in free water. Moreover, water activity is one of the most crucial factors related to the classification criteria for semi-dried restructured sausages ( Jang et al, 2015 ), and the safety of microorganisms in semi-dried foods. Water activity between 0.60−0.90 is desirable for intermediate moisture foods ( Aguilera and Gutiérrez-López, 2018 ).…”
Section: Resultsmentioning
confidence: 99%